Back to Mahal Teglinos: New Pharaonic Evidence from Eastern Sudan. Issue 1 (June 2020) - Manzo, Andrea
This article provides a general overview of the archaeological finds which suggest that Eastern Sudan was in contact with Egypt in the second half of the third and into the second millennium BC. The finds and their contexts are discussed, along with their chronology, typology and distribution in order to understand if they arrived in Eastern Sudan via Upper Nubia, the Red Sea coast, or even through the Eastern Desert. Moreover, the discussion highlights how these finds are providing support to the hypothesis that Eastern Sudan may have been a part of Punt. Finally, the contribution of these finds to our understanding of the economic and cultural exchanges between Egypt and inner Africa is discussed. This review also addresses the definition of the Egyptian commodities exchanged for those of inner Africa and the reconstruction of the way contacts between the involved groups took place.